Mechanismen der CO2 Toleranz bei Seeigeln des Genus Strongylocentrotus = Mechanisms of CO2 tolerance in sea urchins of the genus Strongylocentrotus - Stumpp, Meike (2011)
Increasing atmospheric pCO2 due to anthropogenic CO2 emissions are altering the carbonate chemistry of the oceans, inducing a drop in surface seawater pH (pHSW) and [CO32-] and an increase in seawater pCO2 and [HCO3-]. This phenomenon has been termed “ocean acidification” and has lately received considerable public and scientific attention. Atmospheric pCO2 of 1000 ppm and a concomitant decrease in surface ocean pH of 0.4 units can be expected by the year 2100-2300.The organisms examined in this study – echinoids – are keystone species in several ecosystems as well as economically important. Echinoids are characterized by a calcified skeleton in adult as well as larval stages. Calcifying invertebrates have been shown to be relatively vulnerable to CO2 induced changes in seawater carbonate chemistry. In most studies, echinoid adults and larvae responded with reduced growth and developmental rates to elevated seawater pCO2, but the underlying mechanisms are unknown. In order to fill some of the gaps in knowledge, the present work was aimed at characterizing pCO2 induced changes in acid-base regulatory capacity and energy budgets in two sea urchin species, Strongylocentrotus droebachiensis and S. purpuratus. Furthermore, this study investigated the adults’ physiological acclimation potential and studied ‘carry-over’ effects between different life cycle stages in response to environmental hypercapnia. Using feeding rates, aerobic metabolic rates and egestion/excretion rates measured in larval and adult sea urchins exposed to current (approx. 40 Pa, 390 µatm) and elevated pCO2 conditions (100 - 385 Pa, 990 - 3800 µatm), the present study demonstrated that the energy available for growth and development – so called ‘scope for growth (SfG)’ – was reduced in response to hypercapnic conditions and that SfG correlated with observed decreases in growth and development. In S. purpuratus larvae, the reduction in SfG was due to elevated energy demands for maintenance processes as indicated by highly increased metabolic rates ...